Forest stand height predicted from ICESat-2 ATLAS data for forest inventory and comparison to airborne laser scanning metrics - Lang Mait; Tampuu Tauri; Trofimov Heido (Metsanduslikud Uurimused)
The study analysed 2019–2022 summertime canopy height predictions (HICESat) given in ICESat-2 ATLAS dataset ATL08 for hemiboreal forests growing on an area of 40,000 km2 in Estonia around 25.6° E, 58.8° N. In total 12,711 ATL08 20×20 m pixel observations were used from 3,065 forest stands with homogenous canopy structure. Regression modelling was used to explain variability in ground surface elevation estimates, and relationships of HICESat to basal area weighted mean tree height given in the forest inventory database (HFI) and to the 95th percentile of the vertical distribution of airborne laser scanning pulse return (HALS). The other explanatory variables were the ICESat-2 ATLAS observation geographic location, ICESat-2 ATLAS track and beam energy indicators, forest canopy cover, evergreen coniferous tree dominance indicator, and deep peat soil indicator. The linear model between the Estonian digital terrain model elevation and ATL08 ground elevation had a determination coefficient of R2=99.97% and residual standard error of δ=0.51 m when a geographic location was included. The HFI can be predicted from HICESat with R2=85% and δ=2.7 m. A comparison of means indicated that, on average, HICESat was about 0.3 m greater than HFI. All the predictive variables (except the geographic location) were significant in canopy height models, and the best models fitted HICESat with R2=95% and δ=1.6 m, however, there was no notable increase in R2 if more predictors than HALS were added in the models. In practical applications using ATL08 data for forest inventories, the inclusion of weak energy beam observations increases the number of observations, but the beam energy indicator has to be included in the models.